Prostitution and attachment styles among young adults in Iloilo City. - Melgarejo, Karol Joy Marchs B. (2005.)
This study sought to: a)find out the reasons of the young adult prostitutes for engaging in prostitution; b)Know the attachment styles of young adult prostitutes and younf adults who do not engage in prostitution and; c)to demonstrate the relationship between prostitution and attachment styles among young adults. Sixty (60) young adults who were prostitutes (30) and who did not engage in prostitution (30) served as participants of this study. the design of the study was descriptive-correlational. A Revised Version of Brennan and Shaver's Attachment Questionnaire and an Interview Guide were used for data gathering., Results showed that the reasons for engaging in prostitution by the young adult respondents of this study were most frequently related to parental abuses and the need to maintain a lifestyle that is beyond their means. Also the prostitute respondents generally have an avoidant attachment style towards their parents while majority of the young adults who do not engage in prostitution tend to have a secure attachment style towards their parents. It was also revealed through the use of Chi-Square that there is a relationship between prostitution and attachment styles among young adults. These results were generally consistent with the framework of the study.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Prostitutions -- Iloilo City